Effects of motivation domains on social functioning in schizophrenia with consideration of the factor structure and confounding influences. (January 2021) - Uchino, Takashi; Nemoto, Takahiro; Kojima, Akiko; Takubo, Youji; Kotsuji, Yumi; Yamaguchi, Eriko; Yamaguchi, Taiju; Katagiri, Naoyuki; Tsujino, Naohisa; Tanaka, Kuniaki; Mizuno, Masafumi
Abstract: In patients with schizophrenia, motivation has been assumed to act as an intervening factor between cognitive function and social functioning. Motivation is thought to comprise three domains defined by their orientations: intrinsic motivation, extrinsic motivation, and amotivation. Although these orientations can confound each other, the effects of motivation domains on social functioning remain obscure. We investigated these relationships after confirming the factor structure of social functioning using the Social Functioning Scale (SFS). A total of 97 stable outpatients with schizophrenia were recruited. In addition to the SFS, the General Causality Orientations Scale (GCOS) was used to measure the motivation domains. First, we examined the factor structure of the SFS using exploratory and confirmatory factor analyses. Next, we conducted structural equation modeling to examine the effects of motivation domains on social functioning. The SFS showed a two-factor structure: interpersonal and intrapersonal functioning. The structural equation model revealed that (1) amotivation was negatively related to both intrapersonal and interpersonal functioning, (2) intrinsic motivation was positively related only to intrapersonal functioning, and (3) extrinsic motivation was positively related only to interpersonal functioning. Each motivation domain was associated with different factors of social functioning. Future interventions aimed at improving social functioning should consider these motivation domains based on their orientations. Cognitive remediation accompanied by considerations for and approaches to each of the domains may maximize recovery in patients with schizophrenia.